EKSISTENSI LEMBAGA ADAT WAPULAKA DALAM PENYELESAIAN SENGKETA TANAH - Ayusni Ayusni; Jabal Nur; Nur Intan; Heryanti Heryanti (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
This study aims to determine the existence and the role of Wapulaka Customary Institution in settling land disputes in Bahari Village, Sampolawa District, South Buton Regency. This study is a normative empirical research with field research taking place in Bahari I, II and III villages also known as Wapulaka villages through observation and interview methods. The results of study indicate that in settling community land disputes, the existence of Wapulaka customary institutions is still significant, especially in assisting the village government. The role of functionaries of traditional institutions determines a successful dispute resolution where the Sara Adati Wapulaka is the reference. The settlement of land disputes is carried out by Wapulaka customary institutions through deliberations where Sara Adati Wapulaka acts as a mediator so that the disputing parties can reach an agreement and peace.